Археологічні дослідження в Чутівському та Новосанжарському р-нах Полтавської обл. у 2006—2008 рр. - Коваленко, О.В.; Луговий, Р.С. (Археологічні дослідження в Україні, 2009)
Publication deals with the results of investigations of six barrows with burials of the Late Sarmatian time near Storozhove village in Chutovo Region of Poltava Oblast. The site is considered to be a family necropolis with Sarmatian burial rite, but the inventory is typical for Chernyakhivska culture. Also, the article describes the results of investigations at Tatarskyi Buhor settlement near Klusivka village in Novi Sanzhary Region of Poltava Oblast, where materials of Neolithic, Copper and Bronze Ages and Scythian time have been identified.